Kemampuan Literasi Informasi Generasi Milenial pada Pemustaka di Perpustakaan UIN Sunan Ampel Surabaya - Aries Hamidah; Isna Fistiyanti (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
The application of information literacy at Sunan Ampel Surabaya UIN has been carried out since 2001 until now. In the course of implementing Information Literacy, it was deemed important by researchers to conduct research on mastery of literacy skills using an empowering eight model. The results of the study show that not all components of literacy skills mastery using the Empowering Eight model are controlled by millennial generation users. The eight empowering component that has not been mastered by the user is the identification of topics, namely in mastering skills in the search strategy by using Boolean operator tracking strategies, trunscuation and deduction. While the Empowering Eight component that is most controlled by the user is a component of exploration of information sources, organizing, creating information, presentations, evaluating outputs and applying inputs can be categorized as good. In activating the Information Literacy program the Library of UIN Sunan Ampel Surabaya also optimizes literacy activities with audiovisual media, collaborates with various parties and provides facilities and infrastructure that support information literacy activities, such as information literacy programs, and various promotions.